1999
DOI: 10.1634/theoncologist.4-3-256
|View full text |Cite
|
Sign up to set email alerts
|

A Staff Dialogue on Do Not Resuscitate Orders: Psychosocial Issues Faced by Patients, Their Families, and Caregivers

Abstract: Shortly before his death in 1995, Kenneth B. Schwartz, a cancer patient at Massachusetts General Hospital (MGH), founded The Kenneth B. Schwartz Center at MGH. The Schwartz Center is a non‐profit organization dedicated to supporting and advancing compassionate health care delivery which provides hope to the patient, support to caregivers, and encourages the healing process. The Center sponsors the Schwartz Center Rounds, a monthly multidisciplinary forum where caregivers reflect on important psychosocial issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
2
0
2
Order By: Relevance
“…Ten articles (50% of those selected) [8][9][10][11][12][13][14][15][16][17] dealt with different aspects of the EOL care of oncohematologic patients from the caregiver point of view. These aspects included (see Table 3):…”
Section: Resultsmentioning
confidence: 99%
“…Ten articles (50% of those selected) [8][9][10][11][12][13][14][15][16][17] dealt with different aspects of the EOL care of oncohematologic patients from the caregiver point of view. These aspects included (see Table 3):…”
Section: Resultsmentioning
confidence: 99%
“…Los clásicos decían cosas inteligibles pero difíciles de aceptar, como que es más digno del hombre sufrir el mal que hacerlo. Ponderamos como hermoso el pensamiento de que lo que realmente frustra una vida no es el dolor, sino la falta de amor; que el gran fracaso de una vida es haber vivido sin amar 3,17 . Es decir, palpamos un valor escondido en los momentos de prueba, y la existencia de valor en nuestra vida va unida a su sentido.…”
Section: ¿Tiene "Utilidad" La Vida Espiritual?unclassified
“…A review of the literature in this area has found very little research about how patients and their families would like discussions surrounding resuscitation to take place [11,14,19,20]. Published work suggests that not only do there appear to be concerns over how to conduct resuscitation discussions but also how to communicate resuscitation decisions to the wider health-care team [5,19,21].…”
Section: Introductionmentioning
confidence: 99%